PENGARUH PUPUK ORGANIK PADAT TERHADAP HASIL BEBERAPA VARIETAS KEDELAI ( Glycine max (L)Merr) PADA TANAH VERTISOL - Wiyono; Achmad Fatchul Aziez; Agus Budiyono; Setie Harieni; Dwi Susilo Utami (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Soybean (Glycine max (L.) Merr.) was one of the food commodities whose the demand has not been fulfilled. Local soybean production is predicted to stagnate in the range of 520,000 tons, while consumption is estimated to reach 3.07 million tons. The causal factor is suspected to be due to limited soil water supplies and unsuitable physical properties of the soil, especially in Vertisol . The purpose of this study was to determine the effect of organic fertilizer doses on several soybean varieties on Vertisol. The study design uses the Split Plot Design. As Main Plot are Varieties (Grobogan, Burangrang, and Baluran Varieties), while as Sub Plots are Doses of Organic Fertilizers (0, 10, 20, and 30 tons / ha). The data obtained were analyzed by Analysis of Varians. Then carried out further tests with the DMRT test (Duncan Multiple Range Test) at a significant level of 5%. The results showed that the administration of organic fertilizer at a dose of 30 tons / ha increased the yield of all soybean varieties tested, while the administration of organic fertilizer below that dose only increased in vegetative growth. Baluran varieties provide the best response to the provision of organic fertilizer, following Burangrang, and Grobogan.